KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS FALSE TEETH EXTRACTION AMONG THE COMMUNITY MEMBERS OF ATANGA SUB-COUNTY, PADER DISTRICT. A CROSS-SECTIONAL STUDY. - Ocen , Howard; Ojok , Godfrey P Kingston (Student’s Journal of Health Research Africa, 2023)
Background. The Global Burden of Disease Study (2017) estimated that oral diseases affect 3.5 billion people worldwide, with untreated dental caries being among the most prevalent non-communicable diseases (WHO, 2017). The main objective of this study was to determine the factors affecting the utilization of oral and dental services at Katate Health Centre IV, Kanungu district. Methodology. A descriptive cross-sectional study was done on 61 randomly sampled respondents from whom data was collected using a questionnaire and then analyzed using SPSS version 21. Results. Affecting Utilization of Oral and Dental services include traditional beliefs (4.6%), traditional healers being part of dental care (67%), use of native herbs (63.9%), lack of awareness (80%), myths and misconceptions (21.3%) and some believe that dental caries and tooth extractions do not require medical interventions (9.8%), high costs of dental service (71%), unemployment (19.7%), lack of insurance (75%), low levels of education (77%), and low family income (50.8%). Poor transport systems (55.7%), long distances (47.4%), poor relationship with the health workers (23%), long waiting times and delays (19.7%), lack of confidentiality (29.5%), inconveniences at oral and dental care clinics (32.8%). Conclusion. There were many factors identified from this study that affected the uptake of oral dental services. Individual factors were traditional beliefs and traditional healers, myths, and misconceptions. Socioeconomic factors were unemployment, low education levels, low family income, and high costs. Health system-related factors were long waiting times, lack of confidentiality, and poor relationship with health workers. Recommendation. There is a need for the administration of Katate Health Centre IV in Kanungu district in conjunction with the Ministry of Health to ensure that dental services including dental equipment, sundries, drugs, and medical dental practitioner available for clients at every level of health care.